Developing PMRI-based E-worksheets integrating mandi kasai cultural context to enhance students’ understanding of relations and functions - Idul Adha; Anna Fauziah; Azka Nur Azifah; Rani Refianti; Lucy Asri Purwasi (CV. FOUNDAE, 2026)
Background: Relations and functions are fundamental mathematics topics that require students to connect abstract concepts with real-life situations. However, students’ conceptual understanding remains limited due to the abstract nature of the material and the lack of contextual digital learning resources integrating local culture. Aims: This study aimed to develop a PMRI-based e-worksheet integrating the Mandi Kasai cultural context and to evaluate its validity, practicality, and effectiveness in learning relations and functions. Method: This Research and Development (R&D) study adopted the ADDIE model, including analysis, design, development, implementation, and evaluation stages. The participants were eighth-grade students at SMP Negeri 4 Lubuk Linggau City. Data were collected through expert validation sheets, teacher and student response questionnaires, and learning achievement tests, and analyzed using descriptive quantitative techniques. Results: The e-worksheet obtained validity scores of 91% from material experts, 93% from media experts, and 96% from language experts. Practicality reached 89.33% based on teacher responses and 93.34% based on student responses. The learning effectiveness analysis produced an N-gain score of 0.67, indicating a moderate improvement in students’ understanding. Conclusion: The PMRI-based e-worksheet integrating the Mandi Kasai cultural context is valid, practical, and effective for supporting students’ understanding of relations and functions.